Analytics of Systemic Crises and the Role of Global Financial Safety Nets. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In response to the global crisis, the Fund overhauled its lending toolkit and boosted its resources, strengthening its ability to pre-empt financial crises. This paper-with the companion paper onaMapping Cross-Border Financial Linkages-takes another look at the recent global crisis in the context of a broader review of past systemic crises to (i) assess whether rising linkages across countries is a source of latent systemic instability and (ii) ascertain whether the global financial safety net (GFSN) is adequate to contain crisis and contagion risks arising from such systemic instability. This paper develops a new methodology to identify systemic crises and reviews associated policy responses from a global, rather than country-level, perspective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet